EVALUATION OF THE EFFICIENCY OF TOCILIZUMAB THERAPY IN PATIENTS WITH RHEUMATOID ARTHRITIS BY ULTRASOUND AND X-RAY DATA - Rita Aleksandrovna Osipyants; D E Karateev; E Yu Panasyuk; G V Lukina; A V Smirnov; S I Glukhova; E N Aleksandrova; A V Volkov; E L Nasonov (Научно-практическая ревматология)
Objective: to estimate the time course of changes in the ultrasound signs of wrist joint synovitis in patients with rheumatoid arthritis (RA) during tocilizumab (TCZ) treatment and to determine whether the progression of joint X-ray changes can be predicted by ultrasonography (USG). Subjects and methods. The investigation enrolled 46 patients with the diagnosis of RA that met the American College of Rheumatology 1987 criteria. All the patients were given TCZ during insufficiently effective previous therapy (median DAS28 was 6.7 [range 5.9—7.2]). They were divided into 2 groups: 1) early RA (ERA) with a disease history of less than 2 years (n = 11); 2) RA with a history of over 2 years (n = 35). Hand USG (Voluson-i GE, USA) with a 4—13-MHz linear probe using an energy Doppler (ED) was carried out before and 6 months after therapy. Structural changes were evaluated by hand and foot X-ray study (before and at 12-month follow-up) according to the Sharp method modified by van der Heide. Results. Dynamic evaluation of the ultrasound signs of inflammation indicated a significant reduction in the magnitude of synovitis in accordance with the gray-scale data in both groups and only in the patients with ERA in the ED mode. There was a clear association of the annual increment in joint X-ray changes with the result of estimation of the magnitude of synovitis according to the ED data (r = 0.669; p < 0.01). Conclusion. Wrist joint sonography allows evaluation of the efficiency of the performed therapy in patients with RA and the presence of moderate or severe synovitis, as evidenced by ED, is a predictor for the progression of joint destruction.